The Role Of Digital Experience In Visitor Satisfaction and Environmental Awareness For Sustainable Ecotourism - Pradina Anjarwaty Sukirno; Ida I Dewa Ayu Raka Susanty; Safinah Yulianty Sitania; Melissa Justin Renjaan; Dewi Fitriani (CV Putra Publisher, 2026)
Digital experience has become an important part of ecotourism development because tourists often become familiar with destinations through social media, online reviews, and visual content before visiting. This study aims to analyze the role of digital experience in shaping visitor satisfaction and environmental awareness in the development of sustainable ecotourism in Maluku Tenggara. The study employed a descriptive qualitative approach through semi-structured interviews and field observations. The informants consisted of tourists, tourism managers, local MSME actors, community members, and tour guides. The data were analyzed through thematic coding, including data reduction, theme grouping, and interpretive meaning-making. The findings show that digital experience functions as an initial gateway for the formation of tourist expectations, especially through Instagram, Google Reviews, TikTok, and WhatsApp. Visitor satisfaction is influenced by natural beauty, affordable prices, basic facilities, cleanliness, clarity of information, and the consistency between digital promotion and the actual condition of the destination. Environmental awareness increased when visitors received direct education from managers or guides, supported by digital media such as short videos and QR codes. This study finds that digital experience functions not only as a promotional tool but also as an educational medium that reinforces sustainable ecotourism. The research was conducted at Hoat Tamngil, Rumadian Village, providing a clear local context for the findings.